An injectable composite hydrogel enhances bone regeneration by rescuing impaired mitochondrial biogenesis and fusion of BMSCs under inflammatory conditions - Weizhou Jiang; Zhijie Pan; Zongze Zhang; Xingchen Yan; Praneetha Palasuberniam; Jun Xiao; Jianlin Shen; Donghong Guo; Yang Zhang; Huan Liu (ACS Publications, 2025)
The treatment of severe bone defects remains an unresolved clinical challenge. Injectable hydrogels loaded with drugs or growth factors are considered to offer substantial benefits in the regeneration of bone defects with irregular shapes under complex pathological microenvironments. In this study, an all-silk-derived composite hydrogel was developed for bone regeneration. The methacrylated silk fibroin (SilMA) hydrogel was fabricated for in situ injection and photocuring to serve as a supporting matrix, with the incorporation of platelet-rich plasma (PRP) to promote the migration and pre-differentiation of the bone marrow mesenchymal stem cells (BMSCs) during the early stage, and silk fibroin (SF) microspheres encapsulating berberine (BBR) to regulate BMSCs osteogenesis over an extended period. The composite hydrogels were demonstrated to promote BMSCs osteogenesis by upregulating mitochondrial biogenesis and fusion. Additionally, it was indicated that the impaired osteogenic activity and mitochondrial dynamics of BMSCs under inflammatory conditions can be reversed through the addition of SF-BBR microspheres. Rat calvarial defect repair experiments using the composite hydrogels showed remarkable bone regeneration and an increase in the local mitochondrial quantity. These findings suggest that the SilMA hydrogel compositing with PRP and SF-BBR microspheres shows great potential for bone regeneration through modulating mitochondrial function.